The great divide: rhamnolipids mediate separation between P. aeruginosa and S. aureus - Bru, Jean-Louis; Kasallis, Summer J.; Chang, Rendell; Zhuo, Quantum; Nguyen, Jacqueline; Pham, Phillip; Warren, Elizabeth; Whiteson, Katrine; Høyland-Kroghsbo, Nina Molin; Limoli, Dominique H.; Siryaporn, Albert (Frontiers in Cellular and Infection Microbiology, 2023)
The interactions between bacterial species during infection can have significant impacts on pathogenesis. Pseudomonas aeruginosa and Staphylococcus aureus are opportunistic bacterial pathogens that can co-infect hosts and cause serious illness. The factors that dictate whether one species outcompetes the other or whether the two species coexist are not fully understood. We investigated the role of surfactants in the interactions between these two species on a surface that enables P. aeruginosa to swarm. We found that P. aeruginosa swarms are repelled by colonies of clinical S. aureus isolates, creating physical separation between the two strains. This effect was abolished in mutants of S. aureus that were defective in the production of phenol-soluble modulins (PSMs), which form amyloid fibrils around wild-type S. aureus colonies. We investigated the mechanism that establishes physical separation between the two species using Imaging of Reflected Illuminated Structures (IRIS), which is a non-invasive imaging method that tracks the flow of surfactants produced by P. aeruginosa. We found that PSMs produced by S. aureus deflected the surfactant flow, which in turn, altered the direction of P. aeruginosa swarms. These findings show that rhamnolipids mediate physical separation between P. aeruginosa and S. aureus, which could facilitate coexistence between these species. Additionally, we found that a number of molecules repelled P. aeruginosa swarms, consistent with a surfactant deflection mechanism. These include Bacillus subtilis surfactant, the fatty acids oleic acid and linoleic acid, and the synthetic lubricant polydimethylsiloxane. Lung surfactant repelled P. aeruginosa swarms and inhibited swarm expansion altogether at higher concentration. Our results suggest that surfactant interactions could have major impacts on bacteria-bacteria and bacteria-host relationships. In addition, our findings uncover a mechanism responsible for P. aeruginosa swarm development that does not rely solely on sensing but instead is based on the flow of surfactant.